Economic analysis of lavender production in forest villages of Isparta province - Kader Hale GÜLER; Mehmet KORKMAZ (Turkish Journal of Forestry, 2018)
Increasing the income level of forest villagers has an important role in reducing social pressure on forests. The aims of this study were to do an economic analysis of lavender production and to determine the importance of lavender production at the household level and in the local economy in the forest villages of Isparta province. The research was conducted in Aydoğmuş, Kılıç, Çukurören and Kuyucak villages. It was determined internal rate of return (IRR) is 22.59%for wet lavender and 29.24%for dry lavender as a result of economic analyses. Lavender production was found economically for both investments (wet and dry) because the current interest rate of the Central Bank is 13.37% for the year 2017. Income from lavender cultivation at the household level constitutes approximately half (48.8%) of crop production income and 37% of total income. The capital employment rate for dry lavender was found to be 36506.95 TRY/person and for wet lavender it was found to be 83235.84 TRY/person.